Fish biodiversity and community structure of the Okpara stream, Oueme River, Benin, West Africa: Risk of high predation and food-web alteration - SIDI IMOROU, Rachad; ADITE, ALPHONSE; ADJIBADE, Nambil Kayodé; ARAME, Hamidou; SONON, Pejanos Stansilas; ABOU, YOUSSOUF (My University, 2019)
Despite their economic and commercial importance for grassroots, and the high degradation pressure of their habitat, the fishes of most African riverine ecosystems are unknown. The current study aimed to document the diversity and community structure of the Okpara stream (Oueme River) fishes in order to contribute for habitat protection, speciesconservation and valorization. From December 2015 to May 2017, fish samplings were made monthly on five collecting sites with gill net, hooks and cast net. Overall, 53 fish species belonging to 30 genera and 14 families were inventoried with Mormyridae (9 species) and Cichlidae (8 species) the most speciose taxa. Numerically, 15 species aggregating 92.14% dominated the fish community with Hemichromis fasciatus (29.20%), the most dominant species. The high abundance of Hemichromis fasciatus, a top piscivorous cichlid, suggested a high predation that may affect the food web and the ecosystem balance. The multiple degradation factors recorded require a holistic management scheme including ecotoxicological studies, water hyacinth biocontrol, habitat protection, species conservation / valorization and ecosystem follow-up.
Keywords: Degradation; Food-web; Hemichromis; Management; Oueme; River; Predation